Keabsahan dan Akibat Hukum Perkawinan yang Dilaksanakan dengan Pemalsuan Identitas - Mohammad Akbar Sudarso; Surahmad Surahmad (Jurnal USM Law Review)
The purpose of this research was to explore the Indonesian legal perspective on identity falsification in marriage, especially in the context of the validity and legal consequences of this action. Marriage is a physical and mental bond between a man and a woman husband also wife, purposed to hold happiness and also create an eternal family (household) based on the Almighty God, regulated in Law Number 1 of 1974 concerning marriage. Falsification of identity in marriage, as evidenced in the Jambi District Court decision 265/pid.sus/2022/PN jmb, is a prevalent issue. This research employs a normative juridical research technical using a case approach also a statutory approach. The findings indicate that identity forgery in marriage can invalidate the marriage, as per the Jambi District Court decision 265/pid.sus/2022/PN jmb. However, this case highlights the lack of justice for the victim/witness, namely Nuar Aini Yuni Saputri. There are still material and immaterial losses that have not been fulfilled, including the victim's family not receiving back the money from the defendant's fraud. Moreover, the victim continues to face harassment due to her invalid marriage. This research emphasizes the urgency of addressing identity falsification in marriage within the Indonesian legal framework. It also underscores the need for justice to be served fully, ensuring that victims of identity falsification receive appropriate restitution and protection from further harm.